A cross-sectional study on the quality of life of patients with peripheral diabetic neuropathy pain in Hospital Tengku Ampaun Afzan, Kuantan, Malaysia - Abdullah, Sinan Mohamed; Abdul Razak, Tariq; Nik Ahmad, Nik Nur Fatnoon; Mohamed, Abdul Hadi; Che Abdullah, Shahrin Tarmizi (Pharmacotherapy Group Faculty of Pharmacy University of Benin, Benin City Nigeria, 2018)
Purpose: To evaluate the quality of life of patients with peripheral diabetic neuropathy pain (PDNP) in Hospital Tegku Ampaun Afzan (HTAA), Kuantan, Malaysia. Methods: Ninety (90) participants were selected from the Medical Outpatient Department (MOPD) clinic of HTAA. The study adopted a cross-sectional design, and the self-administered Douleur Neuropathy 4 (DN4) and Audit of Diabetes-Dependent Quality of Life (ADDQoL) questionnaires were used for data collection. Results: The negative impact of diabetes on QoL was clearly reflected in the fact that every domain had a negative mean value. Overall, 27.8 % of the participants reported that DM negatively affected their QoL and 37.8 % expressed the opinion that their QoL would have been higher if they were not diabetic. QoL correlated with marital status and age, with married participants and participants in the age range 50 - 59 years old showing QoL negatively affected (p < 0.05) by DM with PDNP. Apart from diabetes type, all other characteristics significantly affected participants QoL as reflected by the various related domains (p < 0.05). Conclusion: Based on the findings of this study, it seems that individuals with diabetes and PDNP have a low QoL, with regard to “freedom to eat”, “freedom to drink”, “physical health”, “family life”, and “living condition”.